Quality of public transportation in Aracaju, Se - Ferro, S. R. O. P. B.; Melo, C. M.; Fonseca, V. (Scientia Plena, 2012)
Urban transport, especially buses, is still the system used by most of the population to the need to shift their daily activities. This study, conducted in Aracaju-SE, with students from two universities, was aimed at determining their experience and perception of the conditions of service to users of public transport, respect for their rights and the environment. This research, descriptive and exploratory, was qualitative, using descriptive statistics for analysis.